8. If p(x) = 4+3x-x
2
+5x3
, find p(-2)
Answers
Answered by
5
Answer:
p(-2) = -46
Step-by-step explanation:
Given
p(x) = 4 + 3x - x² + 5x³
we get p(-2) by substituting -2 for each x in the formula:
p(-2) = 4 + 3×(-2) - (-2)² + 5×(-2)³
= 4 - 6 - 4 - 40
= -46
Hope this helps!
Answered by
5
Step-by-step explanation:
p(2)= 4+ 3(2) - (2)² + 5(2)³
= 4 + 3x2 - 2x2 + 5(2x2x2)
= 4 + 6 - 4 + 5(8)
= 4 + 2 + 5x8
= 6 + 40
= 46 Ans
Similar questions
Math,
6 months ago
Math,
6 months ago
Hindi,
6 months ago
Social Sciences,
1 year ago
Math,
1 year ago